PENGARUH LATIHAN KNEE-TUCK JUMP TERHADAP POWER OTOT TUNGKAI TIM BOLA VOLI PUTRA SMA N 16 PEKANBARU - Richard Parsaulian; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research was conducted to find out if there is the effect of knee-tuck jump exercise towards limb muscle power on men’s volleyball team of Senior High School 16 Pekanbaru. Type of research used is experiment and using one grup preetest-posttest design. Population this research is men’s volleyball team of senior High School 16 Pekanbaru is the entire populations of 9 peoples. While the sample technique used is total sampling (saturated sample) where all the population is sampled. The sample in this amounted to 9 peoples of men’s volleyball team of senior High School 16 Pekanbaru. The instrument used vertical jump. After that, the data is processed with statistics, normality test with lilifors test at significance level ɑ (0.05). The hypothesis is The Effect Of knee-tuck jump Exercise Toward limb Muscle Power In men’s volleyball team of senior High School 16 Pekanbaru. Based on the analysis of statistical data, there are an average pree-test 36,11 and an average post-test 40,56, then the data is normal with an increase of 4,44 . Based on t test analysis produces t hitung = 15,31 > t tabel = 1,860. Meaning t hitung > t tabel. Thus, there is the effect of knee-tuck jump exercise towards limb muscle power in men’s volleyball team of senior High School 16 Pekanbaru. Keywords: Knee-Tuck Jump , Limb Muscle Power